MODULASI DAN DAN KEAKURATAN TERJEMAHAN SUBTITLE THE LEGEND OF KORRA 4 - Multazim, Akhmad (English Education:Journal of English Teaching and Research, 2019)
This research aims to find out the types of modulation procedure in the subtitle of the legend of Korra season 4 and describe the accuracy of the subtitle of the movie. This descriptive qualitative research applied total sampling technique consisting 78 data. The data are subtitles containing modulation procedure taken from English and Indonesian subtitle of the legend of Korra season 4 and its accuracy assessment. To collect the data, I transcribed subtitle and distributed questionnaire to raters to assess translation accuracy. I used Vinay dan Darbelnet’s theory of modulation procedure and Nababan’s theory of translation accuracy assessment. The result of the research shows that there are 8 out of 10 types of modulation procedure; Abstract for Concrete (10 data), The Part for The Whole (6 data), One Part for Another (5 data), Reversal of Terms (14 data), Negation of Opposite (5 data), Active to Passive (29 data), Space For Time (4 data) and Exchange of Intervals For Limits (5 data). Active to Passive was the most dominant type used in the subtitle. Out of 78 data, 49 data (62,82%) are accurately transferred. It can be concluded that the subtitle of the legend of Korra season 4 is accurate.